Medical appointments and provision of medical care during the COVID-19 pandemic in Mainz, Germany. - Markus Schepers; Irene Schmidtmann; Daniela Zahn; Philipp Wild; Manfred Beutel; Alexander K Schuster; Thomas Münzel; Karl J Lackner; Katharina Geschke; Jörn Schattenberg; Rieke Baumkötter; Simge Yilmaz; et al. (PLoS ONE, 2023)
Previous evidence suggested that non-COVID-19-related medical care was reduced during the first wave of the COVID-19 pandemic, but it remained unclear whether or to which extent this effect lasted beyond the first wave, or existed in a longer time frame. Here, we consider questionnaire data of the Gutenberg-COVID-19 study together with pre-pandemic baseline data of the Gutenberg Health Study concerning the region around Mainz, Germany, to study the effects of the pandemic on the provision of medical care until April 2021. We observed that the proportion of cancelled medical appointments was low and that the fraction of participants with a medical appointment as an indicator for the number of appointments being made was in line with pre-pandemic levels. Appointments were more likely cancelled by the patient (rather than the provider), and more likely cancelled by medical specialists such as dentists or ophthalmologists (rather than GPs). In conclusion, we found some evidence that, at least with regard to realized appointments, the medical system and the provision of medical care were not harmed by the COVID-19 pandemic on a longer time scale.